12th Five Year Plan (2012-17) and Annual Plan (2012-13) Volume-I Government of NCT of Delhi - Planning Commission (Planning Commission, 2012)
During the period of the Twelfth Five Year Plan (2012-2017) we look forward to Delhi emerging as a Caring City; a city in which the citizens proudly aspire to and secure a future for themselves and their children. Good City to live in and a city that caters to the needs of all sections of society. Productive City that fulfils the needs of the productive and creative citizenry. Therefore, the underpinning principles of our vision for Delhi in the new five year plan is of a Good, Productive, and Caring city. We will reach out to all those who toil ceaselessly and help to build this city.
Planning Department Government of NCT of Delhi